Comparative Liquidity Management Analysis Between Islamic Commercial Banks (BUS) and Islamic Business Units (UUS) Using the NPF and FDR Framework - Ririn Aulia Nikman; Sri Nuraulia; Ayu Ariska (JOURNAL EKONOMI, KEUANGAN, PERBANKAN DAN AKUNTANSI SYARIAH, 2025)
This study aims to analyze and compare liquidity management practices between Islamic Commercial Banks (BUS) and Islamic Business Units (UUS) in Indonesia, using Non-Performing Financing (NPF) and Financing to Deposit Ratio (FDR) as primary indicators. A descriptive-qualitative approach is employed, utilizing secondary data from OJK reports, Bank Indonesia publications, and peer-reviewed journals from 2020-2025. The findings reveal a significant dichotomy in liquidity strategy and risk profile. BUS maintains an optimal FDR of 84.77%, indicating balanced intermediation with strong profitability (ROA 2.04%) and controlled financing risk (NPF 2.12%). Conversely, UUS exhibits an excessively high FDR of 112.37%, signaling aggressive financing expansion beyond mobilized third-party funds, accompanied by a critical NPF of 7.75% and low efficiency (BOPO 90.61%), demonstrating structural dependency on parent conventional bank funding. The study confirms that FDR alone is insufficient to assess liquidity health without integrating NPF as a moderate variable. High FDR without commensurate asset quality generates funding liquidity risk and undermines long-term stability. This research contributes a novel comparative typology of liquidity behavior in dual-banking systems, showing that UUS operate under a distinct risk paradigm requiring differentiated regulatory treatment